Food and feeding behaviours of Spotfin Swamp Barb Puntius sophore (Hamilton, 1822) of Singhiya River, Biratnagar - Risal, Anjali; Shrestha, Samjhana; Mahaseth, Vinod Kumar (Our Nature, 2019)
The present work attempt to present a novel approach about the food and feeding habits of Puntius sophore collected from Singhiya River, Biratnagar. For the study 120 specimens were collected on the monthly basis from March to August 2019, direct from the river with the help of local fisherman. On the basis of percentage of occurrence of gut content analysis the most preferred food item was Green algae (40.6%) followed by diatoms (16.10%), crustaceans (13.50%), protozoan (9.20%), detritus and debris (8.40%), insect larva (7.70%) and rotifers (4.50%). Relative gut length was the lowest at size 4.4-5.1 cm SL and the highest value at size 9.3-10 cm SL. Gastro somatic index was highest peak at the size of 4.4-5.1 cm SL, which indicate the voracious nature of fish at smaller size. The standard length and body weight show a positively significant with alimentary canal length (r=0.878) and alimentary canal weight (r=0.86.4), respectively. The food and feeding behavior of this fish showed that it is omnivores in nature.